Realization of new mechanism of strategic and project management innovative development of national economy (Economics and region, 2018)
In the article are presented results of technical researches and developed practical recommendations, which are needed for creation and organization of effective work of modern mechanism of strategic and project management innovative development of the Ukrainian economy and its hi-tech scientific-production systems (HSPS). For this purpose authors of the article offered  to use a new algorithm, procedures and instruments of realization for «turnkey» national and other having a special purpose programs of development of Ukraine and it HSPS in the most perspective industries of the real sector of economy. In basis of algorithm is fixed acknowledged in the world model of synchronous development of the national innovative system and hi-tech production, by the key element of which HSPS are. After the destiny and maintenance these systems are new enough for Ukraine program-oriented organizational-economic structures. They are able to execute the complete innovative cycle of creation of the newest scientific products jointly with high technologies and systems of production, and also to provide its successful realization on the competitive markets of the whole world, including Europe, America and Asia. In addition, during research was developed and offered order of integration and management the national and special programs of development of economy and hi-tech scientific – production systems during all life cycle. This process is executed on the basis of general and special standards of strategic, multiproject and project management, which are examined in the article. These standards take into account the best experience of innovative and hi-tech progress in front-rank countries and companies which are the leaders of world economy, and also are adapted and intended for the use in the modern terms of Ukraine. They allow to realize the innovative model of development with the use of the newest achievements of science and technologies on the Ukrainian enterprises.Wide use of the offered mechanism and standards of management the programs of social-economical and innovative development of Ukraine, its subsystems and managing subjects will promote the acceleration of processes of integration of national economy and all state in European Union.
Keywords: innovative development of national economy and its hi-tech scientific systems; standards of managing having a special purpose programs of development